Obtención de metales a partir de lodos peligrosos de la industria galvánica (2018)
The present work of degree shows a proposal for the recovery of heavy metals contained in hazardous waste coming from a company of the galvanic sector; the project was developed in three phases: in the first one, the characterization of the residual sludge was found, finding tin (Sn) as a non-aqueous majority component with a percentage of 19.3% in wet base, in the second phase, the bibliographic review was made for select the variables and parameters involved in the leaching and electrolysis processes, and the third phase consisted in the experimental development of said processes. The leaching was carried out by means of magnetic stirring at 750 rpm and a solids concentration of 27% was selected from the rheological analysis of the sludge; initially, it was proposed to evaluate each trial during 420 min, however, when comparing the results obtained by using three leaching agents (HCl, H2SO4 and C6H8O7) with 1 M concentration, it was observed that there was no significant variation in the recovery percentage after 240 min for the case of sulfuric acid (H2SO4), which was selected as the best leaching agent; the use of hydrogen peroxide (H2O2) as an oxidizing agent at four concentrations (0%, 2%, 3% and 5% P/V) and it was determined that the addition of this favored considerably the solubility of undesired compounds, finally the effect of the temperature was evaluated at 22 °C, 40 °C, 60 °C and 80 °C obtaining higher recoveries as the temperature increased; the highest tin recovery was 47.9% and occurred in the test conducted with 1 M H2SO4, t = 240 min, rpm = 750 and T = 80 °C.